Sexuality health programs curricula assessment - Shaughnessy, Erin (Kansas State University, 2009)
The alarming incidence of sex-related health problems among American adolescents has health educators searching for effective curricula-based programs aiming at behavioral changes. Such desire and urgent need to find or create programs and curricula that work have generated different approaches, philosophies, and educational strategies. However, this also may have produced a number of programs that have not benefited from a careful and thorough evaluation: neither evaluation of content, message, and cognitive and/or behavioral effect. The focus of this paper is on the curricula utilized in sexuality health programs in middle and high schools. Questions arise about the impact of these programs. Currently, abstinence-based programs are the only ones funded by the government. Research data does not convincingly show that abstinence-only sexuality education significantly decreases the number of adolescents engaging in sexual intercourse prior to marriage. This paper attempts to review current research about abstinence and comprehensive curricula. I begin by discussing the different approaches and their supporters. The importance of adolescent development and theory will be incorporated into my review. Effectiveness of each approach, as well as evaluation studies will be examined. From this review, I composed my own assessment of one abstinence-based curriculum and one comprehensive based curriculum.
Keywords: Sexuality education; Abstinence sexuality education; Comprehensive sexuality education; Health Sciences, Public Health (0573)